A DEAD‐box RNA helicase Ddx54 protein in oligodendrocytes is indispensable for myelination in the central nervous system. Issue 3 (14th December 2012) - Zhan, Rui; Yamamoto, Masahiro; Ueki, Toshiyuki; Yoshioka, Nozomu; Tanaka, Kayoko; Morisaki, Hiromi; Seiwa, Chika; Yamamoto, Yuta; Kawano, Hitoshi; Tsuruo, Yoshihiro; Watanabe, Kenji; Asou, Hiroaki; et al.
Abstract We recently reported that a new monoclonal antibody, 4F2, which labels oligodendroglial lineage cells, recognizes a DEAD‐box RNA helicase Ddx54 and that Ddx54 binds to myelin basic protein (MBP) in brain and cultured oligodendrocytes. To elucidate the biological function of Ddx54, we generated a recombinant adenovirus, Ad‐shRNA:Ddx54, expressing a short hairpin RNA to silence endogenous Ddx54 protein. The virus was intraventricularly injected into the brains of mice on postnatal day (PD) 2. The brains at PD 9 were then analyzed by immunohistochemistry. In untreated normal brain sections, as well as control brains that had been injected with Ad‐β‐Gal, myelination of axons occurred in the corpus callosum with filamentous patterns of immunosignals of myelin‐associated glycoprotein (MAG) and MBP. In Ad‐shRNA:Ddx54‐injected brain, substantial amounts of MAG and MBP immunosignals were present, but MBP immunosignals accumulated in the subplate layer and did not intrude into the emerging white matter. Immunoblot analysis revealed that Ddx54 knockdown caused a significant decrease in the level of 21.5 kDa MBP isoform and Ddx54, but the amount of Olig2; 2′, 3′‐cyclic nucleotide 3′ phosphodiesterase; MAG; three MBP isoforms (14, 17.5, and 18 kDa); and QKI‐5, QKI‐6, and QKI‐7 proteins remained unchanged. Transfection of the Ddx54 expression vector into luciferase reporter‐introduced neuroepithelial cells resulted in upregulated MBP promoter activity. Immunoprecipitation of Ddx54 protein in MBP‐transfected HEK293 cells indicated that Ddx54 may directly interact with MBP mRNA. These results suggest that Ddx54 protein play an important role in central nervous system myelination, presumably in myelin sheath formation after the differentiation of oligodendrocytes. © 2012 Wiley Periodicals, Inc.